A one-dimensional material as a nano-scaffold and a pseudo-seed for facilitated growth of ultrathin, mechanically reinforced molecular sieving membranes. Issue 95 (8th November 2016) - Shamsaei, Ezzatollah; Lin, Xiaocheng; Wan, Li; Tong, Yuping; Wang, Huanting
Abstract : A new pseudo-seeding and nano-scaffolding method was developed to synthesize thin ZIF-8 hybrid membranes (100–200 nm) with remarkable mechanical and structural stability and good gas separation properties. Abstract : A new pseudo-seeding and nano-scaffolding method was developed to synthesize thin ZIF-8 hybrid membranes (100–200 nm) with remarkable mechanical and structural stability and high H2 permeance (2.87 × 10 −5 mol m −2 s −1 Pa −1 ) and selectivity over CO2 (14), N2 (18), CH4 (35), C3 H6 (52.4) and C3 H8 (950.1).